The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1590/s0100-204x2011000900019
|View full text |Cite
|
Sign up to set email alerts
|

Hematological profile of beef cattle with divergent residual feed intake, following feed deprivation

Abstract: -The objective of this work was to characterize the hematological profiles of steers and bulls, according to residual feed intake (RFI), after feed deprivation. Twenty-month-old Nellore steers and bulls were fed feedlot diets for 70 and 56 days, respectively. RFI was calculated as the difference between actual feed intake and expected feed intake. More and less efficient steers and bulls, according to RFI, were subjected to 24 hours of food deprivation. Blood was sampled prior to and following the withdrawal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…There were no statistical differences of variables for blood cell profiles between the efficiency groups for RFI 1 and RFI 2 (Table 6 and Table 7). These results agree with those obtained by Gomes et al (2011), who found no significant differences in the profile of animal blood cells with low or high RFI. On the other hand, Richardson et al (1996) and Richardson et al (2002) described differences in blood characteristics (LEU, HGB, HCR and LYN) measured in progeny of bulls with divergent average genetic values for RFI.…”
Section: Resultssupporting
confidence: 93%
“…There were no statistical differences of variables for blood cell profiles between the efficiency groups for RFI 1 and RFI 2 (Table 6 and Table 7). These results agree with those obtained by Gomes et al (2011), who found no significant differences in the profile of animal blood cells with low or high RFI. On the other hand, Richardson et al (1996) and Richardson et al (2002) described differences in blood characteristics (LEU, HGB, HCR and LYN) measured in progeny of bulls with divergent average genetic values for RFI.…”
Section: Resultssupporting
confidence: 93%
“…Handling of animals during maintenance, transport, and handling before slaughter can also show variations in the blood profile due to stress in cattle. The high ratio of neutrophils can demonstrate stress in cattle compared to lymphocytes (N/L), in addition to high levels of stress hormones in the blood (Gomes et al, 2011;Anton et al, 2016). Variations in the hematological profile can provide information related to oxygen transport, the sensitivity of cattle to stress, and is an indication of animal Advances in Animal and Veterinary Sciences January 2020 | Volume 8 | Issue 1 | Page 112 tolerance to heat and environmental stress (Ariana et al, 2018;Gomes et al, 2011).…”
Section: Advances In Animal and Veterinary Sciences January 2020 | Vomentioning
confidence: 99%
“…In contrast, studying Nellore steers and bulls, no effects of RFI class were observed for the blood parameters hemoglobin and hematocrit (Gomes et al, 2011).…”
Section: Blood Parametersmentioning
confidence: 66%
“…Therefore, heat production can be indirectly estimated from heart rate (HR) after calibration to oxygen consumed per heart beat, based on the fact that oxygen used by homoeothermic animals is transported to the tissues by the heart (Brosh, 2007). In association with heat production, some physiological indicators of FE such as blood parameters have been used, including hematocrit content (Gomes et al, 2011). Since high RFI animals commonly consume more feed than the low RFI ones, this should increase oxygen consumption and thus require a higher capacity of oxygen transportation in high RFI animals (Nkrumah et al, 2006;Chaves et al, 2014;Chaves et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation